Alternatives to routinely used physiotherapy interventions for achieving maximum patients' benefits and minimising therapists' exposure in treatment of COVID-19 – a commentary. (1st November 2020) - Adhikari, Shambhu P.; Dev, Rubee; Sandborgh, Maria
Abstract: The evidence and effectiveness of physiotherapy interventions in treatment of patients with confirmed or suspected coronavirus disease 2019 (COVID-19) is limited. Routinely used interventions in physiotherapy imply a very high risk for physiotherapists because the duration of direct contact with patients is quite long. Physiotherapy may need to be administered by weighing the benefit-risk ratio. Therefore, there is a critical and urgent need to adopt alternatives or modified forms of physiotherapy interventions. As the situation for management of COVID-19 in low-resource contexts could differ from that in high resource context, interventions need to be adapted to the available resources and technology in various settings. Tele-physiotherapy could be a viable option for patients who are in acute care in the hospital, in rehabilitation unit or under quarantine at home due to confirmed or suspected COVID-19. Modification in physiotherapy interventions and adjustment in intervention parameters may serve as an alternative strategy. This article describes alternatives to and/or modification of routinely used physiotherapy interventions for achieving maximum patients' benefits and minimising therapists' exposure in treatment of individuals with confirmed or suspected COVID-19.